A construção performativa da felicidade feminina em tempos de pandemia: uma análise crítica dos discursos da Vogue Brasil - Bianka Macário de Lima (2021)
The so-called female magazines are for decades part of women's daily life in the most different age groups, helping to build meanings and performative speeches (BOURDIEU, 2008) that go beyond just the informative function. That being said, the main goal of this research is to analyze media material from the 2020 editions of Vogue Brasil through the Critical Discourse Analysis (FAIRCLOUGH, 2016; RESENDE; RAMALHO, 2011), in order to identify the performative speeches construction about an ideal of happy woman project during the Covid-19 crysis, pandemic that had a strong impact in the private and daily life, changing in a significant way the social relations, that had even more substantial consequences in the female world. From the critical analysis of 11 media texts of the magazine, based on the categories of the evaluation, interdiscursivity, social representation and general structure, the results presented that the happy woman that Vogue Brasil talks about in the pandemic, was grounded on the search for individual happiness, based on the luxury consumption, in high productivity, in immediacy, in hegemonic beauty standards and success.